Лексико-граматичні трансформації при перекладі патентної документації Великої Британії - Царьова, Світлана Олексіївна; Лобач, В. А. (ПП Цюпак А. А., 2023)
Особливе місце у вивченні науково-технічної літератури англійською мовою займає патентна документація, яка за ступенем складності англійської технічної мови займає одне з перших місць. Патентна література та документація має свої особливості та складності, які необхідно враховувати при перекладі з однієї мови на іншу. Внаслідок технічного прогресу відбувається глобальний розвиток винаходів, який призводить до стабільного збільшення кількості виданих патентів у всьому світі. Саме переклад патентної документації та літератури є одним із найскладніших і затребуваних видів перекладацької діяльності. Патентний переклад характеризується поєднанням ознак технічного та юридичного перекладу. Залежно від предметної галузі винаходу, технічна складова патентного перекладу може відноситися до будь-якої галузі науки та техніки. Актуальність нашої статті полягає у потребі більшого поглиблення у лексико-граматичні трансформації як засіб досягнення адекватного перекладу патентної документації через зростаючу соціальну значимість патенту внаслідок появи все більшої кількості винаходів. Матеріал статті розкриває такі поняття: патент разом із його структурою, лексичні трансформації (конкретизація значень, генералізація значень, контекстуальна заміна, смисловий розвиток і антонімічний переклад), граматичні трансформації (зміна структури речення, перестановка, заміна частин мови, додавання та вилучення). Також у статті представлено не тільки приклади використання перелічених трансформацій, а й прикладний аналіз перекладу уривку англійського патенту українською мовою з використанням перекладацьких трансформацій.

A special place in the study of scientific and technical literature in English is occupied by patent documentation, which takes one of the first places in terms of the degree of complexity of the English technical language. Patent literature and documentation have their own peculiarities and complexities that must be taken into account when translating from one language to another. As a result of technological progress, there is a global development of inventions, which leads to a steady increase in the number of issued patents all over the world. The translation of patent documentation and literature is one of the most difficult and sought-after types of translation activity. Patent translation is characterized by a combination of features of technical and legal translation. Depending on the subject field of the invention, the technical component of patent translation can be related to any field of science and technology. The relevance of our article lies in the need for greater depth in lexical-grammatical transformations as a means of achieving adequate translation of patent documentation due to the growing social significance of the patent as a result of the appearance of an increasing number of inventions. The material of the article reveals such concepts as a patent along with its structure, and lexical transformations, namely: concretization of meanings, generalization of meanings, contextual substitution, semantic development and antonymic translation, and grammatical transformations: change of sentence structure, permutation, replacement of parts of speech, addition, and deletion. Also, the article provides not only examples of the use of the listed transformations, namely an applied analysis of the translation of an excerpt of an English patent into Ukrainian using translation transformations.
Lexical and grammatical transformations in the translation of patent documentation of Great Britain
Keywords: адекватний переклад; граматичні трансформації; лексичні трансформації; науково-технічний текст; патентна документація; прикладний аналіз; adequate translation; applied analysis; grammatical transformations; lexical transformations; patent documentation; scientific text; technical text